Genetic variation in SULF2 is associated with postprandial clearance of triglyceride-rich remnant particles and triglyceride levels in healthy subjects. - Niina Matikainen (Public Library of Science (PLoS), 2013)
Context Nonfasting (postprandial) triglyceride concentrations have emerged as a clinically significant cardiovascular disease risk factor that results from accumulation of remnant triglyceride-rich lipoproteins (TRLs) in the circulation. The remnant TRLs are cleared from the circulation by hepatic uptake, but the specific mechanisms involved are unclear. The syndecan-1 heparan sulfate proteoglycan (HSPG) pathway is important for the hepatic clearance of remnant TRLs in mice, but its relevance in humans is unclear. Objective We sought to determine whether polymorphisms of the genes responsible for HSPG assembly and disassembly contribute to atherogenic dyslipoproteinemias in humans. Patients and design We performed an oral fat load in 68 healthy subjects. Lipoproteins (chylomicrons and very low density lipoproteins 1 and 2) were isolated from blood, and the area under curve and incremental area under curve for postprandial variables were calculated. Single nucleotide polymorphisms in genes encoding syndecan-1 and enzymes involved in the synthesis or degradation of HSPG were genotyped in the study subjects. Results Our results indicate that the genetic variation rs2281279 in SULF2 associates with postprandial clearance of remnant TRLs and triglyceride levels in healthy subjects. Furthermore, the SNP rs2281279 in SULF2 associates with hepatic SULF2 mRNA levels. Conclusions In humans, mild but clinically relevant postprandial hyperlipidemia due to reduced hepatic clearance of remnant TRLs may result from genetic polymorphisms that affect hepatic HSPG.